2015
DOI: 10.1136/bjophthalmol-2015-307128
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy with juxtapapillary laser photocoagulation versus vitrectomy without juxtapapillary laser photocoagulation for the treatment of optic disc pit maculopathy: the results of the KKESH International Collaborative Retina Study Group

Abstract: PPV with JLP for optic disc pit maculopathy had similar functional and anatomic outcomes compared with vitrectomy without JLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 24 publications
8
52
0
2
Order By: Relevance
“…Improvement of vision was achieved in 89% of our cases, with a mean visual gain of almost 3 lines on the Snellen chart at the end of the follow-up time, and 67% had a final BCVA of 0.5 or better. This compares favourably with other functional results [10-14, 19, 22, 25-31]. Similar functional outcomes have been reported by D’Souza et al [16] and Nawrocki et al [17] using the same surgical procedure.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Improvement of vision was achieved in 89% of our cases, with a mean visual gain of almost 3 lines on the Snellen chart at the end of the follow-up time, and 67% had a final BCVA of 0.5 or better. This compares favourably with other functional results [10-14, 19, 22, 25-31]. Similar functional outcomes have been reported by D’Souza et al [16] and Nawrocki et al [17] using the same surgical procedure.…”
Section: Discussionsupporting
confidence: 78%
“…Our results suggest that laser treatment does not aid in anatomical success. This is in keeping with previous studies that have shown similar anatomical outcomes with PPV without juxtapapillary laser photocoagulation for ODP [13, 19-22]. …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations